A survey of liver pathology in needle biopsies from HBsAg and anti-HBe positive individuals. Issue 7 (1st July 2000) - ter Borg, F; ten Kate, F J W; Cuypers, H T M; Leentvaar-Kuijpers, A; Oosting, J; Wertheim-Van Dillen, P M E; Honkoop, P; Rasch, M C; de Man, R A; van Hattum, J; Chamuleau, R A F M; Tytgat, G N J; et al.
Abstract : Aims— To use laboratory data and liver biopsies, prospectively obtained from hepatitis B surface antigen (HBsAg) and anti hepatitis B e antigen (anti-HBe) positive patients, for the assessment of: (1) the relation between biopsy length/number of portal tracts and sampling error; (2) the relation between the severity of piecemeal necrosis and the new grading terminology (minimal, mild, moderate, and severe chronic hepatitis); and (3) liver pathology, which has not been studied in patients with this specific serological profile. Methods —The study group (n = 174) included 104 patients with normal aminotransferase concentrations and no cases with clinically apparent cirrhosis. The specimen length and number of portal tracts were measured at light microscopy examination. Sampling error analysis was related to the discrepancies between aminotransferase concentrations versus histological grade. Detailed histological scorings were undertaken by the reference pathologist and compared with laboratory and hepatitis B virus (HBV) DNA precore sequence data. Results —Sampling error seemed to be a constant feature, even for biopsies ≥ 20 mm, but increased dramatically in biopsies < 5 mm long and/or containing less than four portal tracts. Between 25% and 30% of biopsies, graded as "mild" or "moderate" activity showed features of moderate and severe piecemeal necrosis, respectively. Ten per cent of the patients with normal aminotransferase values had stage III–IV hepatic fibrosis, and 20% had piecemeal necrosis. Only cytoplasmic, not nuclear, core antigen expression was a strong predictor of high hepatitis B viraemia. There was no association between precore stop codon mutations, grade/stage of liver disease, and hepatitis B core antigen (HBcAg) expression. Conclusions —The specimen available for light microscopical examination should be > 5 mm long and should contain more than four portal tracts. In addition, the new grading terminology might give the clinician an inappropriately mild impression of the severity of piecemeal necrosis. Furthermore, even in the presence of normal aminotransferase concentrations, considerable liver pathology can be found in 10–20% of HBsAg and anti-HBe positive individuals; such pathology is not associated with the occurrence of precore stop codon mutations.